2019
DOI: 10.3389/fpsyg.2019.01188
|View full text |Cite
|
Sign up to set email alerts
|

Using Sensors in Organizational Research—Clarifying Rationales and Validation Challenges for Mixed Methods

Abstract: Sensor-based data are becoming increasingly widespread in social, behavioral, and organizational sciences. Far from providing a neutral window on “reality,” sensor-based big-data are highly complex, constructed data sources. Nevertheless, a more systematic approach to the validation of sensors as a method of data collection is lacking, as their use and conceptualization have been spread out across different strands of social-, behavioral-, and computer science literature. Further debunking the myth of raw data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 96 publications
(111 reference statements)
0
12
0
1
Order By: Relevance
“…At issue, then, is determining on a minute by minute basis, to whom each paramedic was communicating. Müller et al (2019), both suggested that multimodal streams of information might be combined to index members' interactions. For instance, Bluetooth data from wearable sensors can permit one to determine which members are within speaking range of others (cf., Kim et al, 2012;Matusik et al, 2019).…”
Section: Use Of Bluetooth Datamentioning
confidence: 99%
“…At issue, then, is determining on a minute by minute basis, to whom each paramedic was communicating. Müller et al (2019), both suggested that multimodal streams of information might be combined to index members' interactions. For instance, Bluetooth data from wearable sensors can permit one to determine which members are within speaking range of others (cf., Kim et al, 2012;Matusik et al, 2019).…”
Section: Use Of Bluetooth Datamentioning
confidence: 99%
“…Sociometers are wearable devices fitted with sensors that can include Bluetooth, RFID and infrared technologies for detecting proximity between individuals, microphones to detect nonverbal vocal activity, and/or accelerometers for detecting physical activity and energy levels [47,71]. If each member of a group is equipped with such a device, then a data set extending over time, multiple individuals, and multiple modalities can be collected.…”
Section: Sociometric Badgesmentioning
confidence: 99%
“…Over time, several designs for sociometers have been developed, with an early example being presented by Choudhury and Pentland, who also coined the term sociometer [10]. Two prominent examples [47] of the latest generation of devices are the OpenBeacon proximity tag [9], from the SocioPatterns Collaboration 1 , and the Rhythm Badge [40] from Massachusetts Institute of Technology (MIT) 2 , which is used in this research.…”
Section: Sociometric Badgesmentioning
confidence: 99%
“…However, when assessing the evidence across the emerging body of research on wearable sensors, it is clear that a single physical measurement cannot be an equally valid indicator for such diverse concepts as "happiness", "friendship", "advice" or "personality". As a consequence, researchers need to address the gap that separates the physical measurement from social or psychological constructs and consider opportunities such as mixed methods in their research design in order to bridge it (Müller et al, 2019).…”
Section: Recommendations and Limitationsmentioning
confidence: 99%